Legal Personality of ASEAN as the Subject of International Law: Contemporary Developments - Satesna, Dhezya Pandu (International Law Discourse in Southeast Asia, 2022)
The Organization of Southeast Asian Nations (ASEAN) has unique characteristics, apart from the legal systems in Southeast Asian countries that are different from one another, but also have different historical aspects. If ASEAN is compared to the European Union, which has the same legal vision, characteristics of society, and even a uniform financial system, ASEAN does not yet have this uniformity. This study aims to identify the legal personality for ASEAN as a subject of international law. This study looks at various theories and concepts regarding international organizations as subjects of international law. This study confirms that the basis for ASEAN legal personality as a subject of international law can be seen in the ASEAN Charter, however, this form of legal personality is still limited.